Islamic Education Curriculum of Ban Budhee School from The South Thailand Muslim Minority - Rohmatun Lukluk Isnaini (STAI Miftahul Ula Nganjuk, 2020)
The Pattani area of Southern Thailand, precisely in the district of Laem Pho, there is a large school called Ban Budhee. It is a royal Islamic-based school that has applied Islamic education curriculum. This study aims to see the components of the curriculum in terms of the limitations of Muslim minority communities in their country in implementing the Islamic education curriculum. This research uses qualitative approach; researcher conducts in-depth interviews, field observation and documentation at the location. This paper focuses on the model of Islamic education curriculum in Muslim minority areas, especially in Ban Budhee School. The Islamic education curriculum is implemented in formal schools and supported by a curriculum held in Tadika (Kindergarten Education Park). Both curriculum are well implemented in meeting the needs of the Muslim community.